2019 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2019
DOI: 10.1109/vr.2019.8798029
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Mental Effort in Virtual Versus Real Environments

Abstract: Is there an effect of Virtual Reality (VR) Head-Mounted Display (HMD) on the user's mental effort? In this paper, we compare the mental effort in VR versus in real environments. An experiment (N=27) was conducted to assess the effect of being immersed in a virtual environment (VE) using an HMD on the user's mental effort while performing a standardized cognitive task (the wellknown N-back task, with three levels of difficulty, N ∈ {1, 2, 3}). In addition to test the effect of the environment (i.e., virtual ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…As for the performance measures, those mainly depend on the type of task. This is also the case for behavioural measures, which have shown to be influenced by MWL, especially in VR [8,9,37,49].…”
Section: Mental Workload Measuresmentioning
confidence: 77%
“…As for the performance measures, those mainly depend on the type of task. This is also the case for behavioural measures, which have shown to be influenced by MWL, especially in VR [8,9,37,49].…”
Section: Mental Workload Measuresmentioning
confidence: 77%
“…Combining ACS and VR has advantages in several application fields. Among the 63 studies retained in this survey, most focused on global VR applications to understand how users felt in a VR context and how to enhance VR application using the user's mental state (i.e., 37 studies) [5,11,13,14,15,16,19,20,29,32,34,36,37,46,47,48,49,55,56,58,60,74,79,83,86,88,89,90,91,98,105,108,113,117,124,140,143]. 10 focused on artificial intelligence (AI) applications by training ACS recognition models in VR [2,21,24,92,93,96,100,121,126,150].…”
Section: Affective and Cognitive Virtual Realitymentioning
confidence: 99%
“…However, for healthy adults, it has been consistently shown that the cognitive load induced by the dual task does not change gait characteristics such as stride length and walking stability but only reduce their walking speed [12]. Compared to reality, it has been shown that subjects could perform the serial N subtraction task equally well in VR [18]. Moreover, the dual task has also been used to investigate the impact of cognitive load on spatial orientation [17].…”
Section: Related Workmentioning
confidence: 99%